A post-hoc analysis of serotype-specific vaccine efficacy of 13-valent pneumococcal conjugate vaccine against clinical community acquired pneumonia from a randomized clinical trial in the Netherlands. Issue 30 (9th July 2019) - Gessner, Bradford D.; Jiang, Qin; Van Werkhoven, Cornelis H.; Sings, Heather L.; Webber, Chris; Scott, Daniel; Gruber, William C.; Grobbee, Diederick E.; Bonten, Marc J.M.; Jodar, Luis
Highlights: Data on serotype specific PCV13 vaccine efficacy (VE) against CAP have not been published. We analysed a randomised controlled trial of PCV13 against CAP among elderly adults. Five of 13 vaccine serotypes had sufficient data for analysis. Statistically significant VE was found for serotypes 3 and 7F and was positive for all five. Abstract: Background: Serotype-specific vaccine efficacy (VE) against adult community acquired pneumonia (CAP) remains poorly defined, yet such data are important for assessing the utility of adult pneumococcal conjugate vaccine (PCV) programs. Methods: We evaluated the Community Acquired Pneumonia Immunization Trial in Adults to assess serotype-specific VE for CAP. This parallel-arm randomized clinical trial assessed 13-valent PCV (PCV13) VE among community dwelling persons aged ≥65 years in The Netherlands. In the original analysis, PCV13 VE against first episodes of vaccine-type (VT) chest radiology confirmed CAP was 45.6% (95% confidence interval [CI] 21.8–62.5%). Unlike the original analysis, we included any subject that met a clinical definition of CAP regardless of radiographic findings. VT-CAP was identified by culture (sterile or non-sterile) or serotype-specific urinary antigen detection (SSUAD) test. Only the five serotypes with at least 10 episodes in the control arm, based on the original analysis, were included for VE assessment. Results: Of 272 clinical CAP visits with VT serotypes identified, 253 (93%) were identified by SSUAD including 210 (77%) by SSUAD alone. VE was determined for serotypes 1, 3, 6A, 7F, and 19A, with total first episodes of, respectively, 27, 36, 25, 38, and 48. VE (95%CI) for the five evaluated serotypes against first clinical CAP episodes were: serotype 1, 20.0% (−83.1% to 65.8%); serotype 3, 61.5% (17.6–83.4%); serotype 6A, 33.3% (−58.6% to 73.2%); serotype 7F, 73.3% (40.5–89.4%); and serotype 19A, 45.2% (−2.2% to 71.5%). Discussion: Statistically significant VE was observed for serotypes 3 and 7F for clinical CAP among elderly community dwelling adults. The VE point estimates and CIs for serotypes 1, 6A, and 19A were lower but consistent with the overall VT-CAP VE of 45.6% previously reported. These findings may be relevant in models to accurately account for the potential impact of adult PCV13 immunization.